2004
DOI: 10.1074/jbc.m311587200
|View full text |Cite
|
Sign up to set email alerts
|

Components of a Pathway Maintaining Histone Modification and Heterochromatin Protein 1 Binding at the Pericentric Heterochromatin in Mammalian Cells

Abstract: Heterochromatin is a higher order chromatin structure that is important for transcriptional silencing, chromosome segregation, and genome stability. The establishment and maintenance of heterochromatin is regulated not only by genetic elements but also by epigenetic elements that include histone tail modification (e.g. acetylation and methylation) and DNA methylation. Here we show that the p33ING1-Sin3-HDAC complex as well as DNA methyltransferase 1 (DNMT1) and DNMT1-associated protein 1 (DMAP1) are components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…Although the chromatin defects observed might reflect indirect effects of Ing1 depletion in the implementation of senescence, the solid evidence linking ING1 to chromatin regulation clearly supports the participation of Ing1 in chromatin changes as the most likely mechanism. Interestingly, it has been proposed previously that p33 ING1 could play a role in HP1 deposition during formation of nascent constitutive heterochromatin (39). One possible explanation for our observation is linked to the reported ability of p33 ING1 to modulate histone acetylation (7,9,39).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Although the chromatin defects observed might reflect indirect effects of Ing1 depletion in the implementation of senescence, the solid evidence linking ING1 to chromatin regulation clearly supports the participation of Ing1 in chromatin changes as the most likely mechanism. Interestingly, it has been proposed previously that p33 ING1 could play a role in HP1 deposition during formation of nascent constitutive heterochromatin (39). One possible explanation for our observation is linked to the reported ability of p33 ING1 to modulate histone acetylation (7,9,39).…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, it has been proposed previously that p33 ING1 could play a role in HP1 deposition during formation of nascent constitutive heterochromatin (39). One possible explanation for our observation is linked to the reported ability of p33 ING1 to modulate histone acetylation (7,9,39). There is clear pharmacological and genetic evidence indicating that histone deacetylation is needed for the tethering of HP1 proteins to chromatin (40 -43).…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, it is formally possible that mSin3 proteins could participate in the establishment of pericentric heterochromatin which required to maintain a euploid genome. Along these lines, it is notable that mSin3A can bind centromeric regions in human cells (Xin et al, 2004), implicating mSin3A in the pericentromeric heterochromatinization process. Thus, the lack of aneuploidy and accelerated tumorigenesis could relate to potential redundancy with the highly related mSin3B homologue which also interacts with mSds3 (Alland et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…ING proteins have been linked functionally to the p53 pathway at different levels, including the control of p53 protein stability, as transcriptional cofactors, or through post-translational modifications of p53 (Nagashima et al, 2001;Nourani et al, 2001;Gozani et al, 2003). ING proteins also participate in chromatin remodelling through their association with histone deacetylases and histone acetyltransferases (Nourani et al, 2001;Feng et al, 2002;Kuzmichev et al, 2002;Vieyra et al, 2002;Xin et al, 2004;Goeman et al, 2005). The most extensively studied member of the ING family is p33ING1, one of the products of the ING1 locus (also referred to as p33ING1b, or ING1b elsewhere; Feng et al, 2002).…”
mentioning
confidence: 99%
“…More importantly, there is ample evidence, both in mammals and yeast, showing that ING proteins can form complexes with histone deacetylases and histone acetyltransferases. Based on this, it has been suggested that ING proteins could play a role in transcriptional control, through chromatin remodelling (Nourani et al, 2001;Skowyra et al, 2001;Feng et al, 2002;Kuzmichev et al, 2002;Vieyra et al, 2002;Xin et al, 2004;Goeman et al, 2005). An increasing number of evidences indicate that ARF can have a direct role in transcriptional control (Kamijo et al, 1998;Rocha et al, 2003Rocha et al, , 2005Calabro et al, 2004;D'Amico et al, 2004;Datta et al, 2004;Kalinichenko et al, 2004;Qi et al, 2004) and, therefore, it is feasible that ARF might cooperate with p33ING1 in transcriptional regulation, through chromatin remodelling processes.…”
mentioning
confidence: 99%